For your eyes only [videorecording (DVD)] - Maibaum, Richard; Wilson, Michael G., 1942-; Conti, Bill; Easton, Sheena; Moore, Roger, 1927-2017; Bouquet, Carole; Topol, 1935-; Glover, Julian; Johnson, Lynn-Holly; Harris, Cassandra; Bennett, Jill, 1930-1990; Gothard, Michael, 1939-1992; et al. (007, 2015)
James Bond is thrust into one of his most riveting adventures in this jam-packed free-for-all of outrageous stunts, passionate encounters and exciting confrontations. Roger Moore portrays Agent 007 with lethal determination in a plot that finds him infiltrating the Greek underworld to find a stolen device capable of controlling a fleet of nuclear submarines!